Challenging the Ideal “Kyai” in the Digital Era 4.0: Gus Iqdam Case Study - Cahyono, Agus Eko; Herawati, Yayuk Widyastuti; Latifah, Nur (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The present research emerges as an answer to the gap in the previous studies above that do not specify preachers who are famous and have many fans not only domestically but also abroad. The preacher perspective provides an explanation of the ideal preacher. This gives the 4.0 generation an understanding of what is worthy of emulation as an endeavour even though the results may differ. The present research was conducted to explore how the reception and rhetoric of Gus Iqdam's preaching and whether the form of mass approach in his preaching in an effort to increase the religiosity of his congregation. The method used in this research is ethnography, which focuses on understanding the culture and social context of a group of people. This process involves direct observation of behaviour and social interactions in natural settings (e.g. in the community, school or workplace). Based on the limited scope of current research, and could be a research gap for future research should examine further in terms of science, socio-cultural context, and its impact on society.